Simulasi Sistem PLTS Atap dan Harga Satuan Energi Listrik Untuk Skala Rumah Tangga di Surabaya - Elieser Tarigan (Jurnal Rekayasa Elektrika, 2022)
Solar energy is a renewable energy source that can be used as a source of electricity using a photovoltaic (PV) system to reduce our dependence on fossil energy. This paper discusses an overview of the use of a rooftop PV system in accordance with applicable regulations in Indonesia. Computer simulation was conducted to determine the potential power and output energy of the rooftop PV system in the city of Surabaya. The simulation was carried out by SolarGIS Pvplanner software. Mathematical equations are derived to estimate the unit price of electric energy for the PV system, and the calculations are done numerically. The simulation results show that the total daily energy average generated from the 3 kWP roof solar PV system in Surabaya is about 13 kWh. Meanwhile, the unit price for PV system electricity is obtained between 0.08 USD - 0.11 USD / kWh.